1992
DOI: 10.1073/pnas.89.23.11297
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate cycling in signal transduction: parafusin, a phosphoglycoprotein and possible Ca(2+)-dependent transducer molecule in exocytosis in Paramecium.

Abstract: Parafusin, a cytosolic phosphoglycoprotein of The background data that tie parafusin to the process of membrane fusion and exocytosis come from studies using the ciliates Paramecium tetraurelia and Tetrahymena thermophila. Paramecium tetraurelia in axenic cultures take up 32p, and phosphorylate a number of polypeptides. The most heavily labeled polypeptide is parafusin, a minor component of Mr 63,000 that shows serine phosphorylation (1, 2). Gilligan and Satir (3,4) showed that, when in vivo-prelabeled wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 12 publications
0
35
3
Order By: Relevance
“…Anti-peptide antibodies made against the derived amino acid sequence of the pPFUS I-4 (see Fig. 4 (4,5). This is in contrast to PGM, which incorporates glucose 1-32P and does not incorporate UDP glucose (21).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Anti-peptide antibodies made against the derived amino acid sequence of the pPFUS I-4 (see Fig. 4 (4,5). This is in contrast to PGM, which incorporates glucose 1-32P and does not incorporate UDP glucose (21).…”
mentioning
confidence: 94%
“…Parafusih has been shown to be phosphorylated via a Ca2+-dependent protein kinase (4). Surprisingly, parafusin is also a phosphoglycoprotein in which a short chain ofmannose residues is 0-linked to serine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case it is thought that the mannose remains associated with the protein while the glucose l-phosphate cycles on and off. Changes in the glycosylation state of PGM and parafusin have been demonstrated to occur in several biological systems [79,80,861, demonstrating that such a cycle is indeed functional in cells. Changes in cytoplasmic calcium levels appear to alter the glucosylation state of both PGM (in the pheochromocytoma PC-12 cell line) [79] and parafusin (in Parumeciunz) [SO].…”
Section: Unique Cytoplasmic Forms Of Glycosylationmentioning
confidence: 99%
“…II, Nov. 1998 7 A series of in vitro experiments later suggested that it was this modification, Glc-1-P that was removed upon exocytosis by a Ca2+-dependent phosphodiesterase, which was defective in the exo-mutant nd9. It was further hypothesized that PFUS might represent a new type of signal transduction molecule involving carbohydrate cycling (Subramanian & Satir 1992).PFUS has been cloned and sequenced and found to have 51% identity to rabbit muscle phosphoglucomutase (PGM), a glycolytic enzyme, although PFUS showed no or minor PGM activity , Levin et al 1998). Compared to PGM, PFUS has several specific insertions and deletions in the primary sequence (Subramanian et al 1994).…”
mentioning
confidence: 99%